Gut Microbiome Characteristics in feral and domesticated horses from different geographic locations - Ang Li; Vinderola Gabriel; Endo Akihito; Kantanen Juha; Jingfeng Chen; Binetti Ana; Burns Patricia; Qingmiao Shi; Suying Ding; Zujiang Yu; Rios-Covian David; Mantziari Anastasia; et al. (172, 2022)
Domesticated horses live under different conditions compared with their extinct wild ancestors. While housed, medicated, and kept on a restricted source of feed, the microbiota of domesticated horses is hypothesized to be altered. We assessed the fecal microbiome of 57 domestic and feral horses from different locations on three continents, observing geographical differences. A higher abundance of Eukaryota (p < 0.05) and viruses (p < 0.05) and lower of archaea (p < 0.05) were found in feral animals when compared with domestic ones. The abundance of genes coding for microbe-produced enzymes involved in the metabolism of carbohydrates was significantly higher (p < 0.05) in feral animals regardless of their geographic origin. Differences in the fecal resistomes between both groups of animals were also noted. The domestic/captive horse microbiomes were enriched in genes conferring resistance to tetracycline, likely reflecting the use of this antibiotic in the management of these animals. Our data showed an impoverishment of the fecal microbiome in domestic horses with diet, antibiotic exposure, and hygiene being likely drivers. The results offer a view of the intestinal microbiome of horses and the impact of domestication or captivity, which may uncover novel targets for modulating the microbiome of horses to enhance animal health and well-being.